Empirical study of the effect of nanocoolant particles on corrosion rate of 316 stainless steel - Asmara, Yuli Panca; Raman, Jeya Gopi; Suparjo, ,; Herlina, Firda; Wei, Yap Chun (Hindawi Limited, 2024)
The advancement of nanotechnology has had an impact on the use of heat exchangers. Nanocoolants, which offer higher thermal efficiency than traditional coolants, have paid significant attention. These innovative fluids, which contain nanomaterials, not only have better heat efficiency but also improve energy efficiency compared to regular coolants. However, the presence of solid nanoparticles in the coolant may cause corrosion and erosion of tubes, leading to massive degradation of those parts. To evaluate the effectiveness of nanocoolant particles, this research was conducted by studying the impact of using nanocoolant on erosion-corrosion occurring on metal surfaces. The study focused on the erosion-corrosion of stainless steel (AISI 316) in coolant solutions containing nanoparticles. The experiments utilized a rotating cylinder electrode (RCE) with rotational speeds ranging from 0 to 1800 rpm and a temperature range of 30°C-70°C. The corrosion rate was determined using the linear polarization resistance (LPR) method, while the erosion was measured by calculating the average surface roughness of the samples. The design of the experiment (DOE) was utilized to find the mathematical expressions of the effects of the nanocoolant on erosion and corrosion. The findings revealed that the corrosion rate and surface roughness of the samples increased with an increase in temperature and rotation speed. Furthermore, the erosion-corrosion effects of the nanocoolant were less significant in stagnant conditions than in flow conditions, and significant differences were observed when compared with conventional coolant. Additionally, synergistic erosion and corrosion processes were detected at higher temperatures and higher rotation speeds for both types of coolants.